Attack of the zittens ebook - Blabey, Aaron (The Bad Guys, 2016)
It's a ZOMBIE KITTEN APOCALYPSE! Should you panic? Should you cry? Should you poop your pants? NO! Just sit back and watch the fur fly as the world's baddest good guys take on Mad Marmalade's meowing monsters! Laugh-out-loud story filled with cool stuff–good guys, bad guys, action, adventure, zombie kittens and a shark in a dolphin suit!